2014
DOI: 10.1371/journal.pone.0097142
|View full text |Cite
|
Sign up to set email alerts
|

Interspinous Spacer versus Traditional Decompressive Surgery for Lumbar Spinal Stenosis: A Systematic Review and Meta-Analysis

Abstract: BackgroundDynamic interspinous spacers, such as X-stop, Coflex, DIAM, and Aperius, are widely used for the treatment of lumbar spinal stenosis. However, controversy remains as to whether dynamic interspinous spacer use is superior to traditional decompressive surgery.MethodsMedline, Embase, Cochrane Library, and the Cochrane Controlled Trials Register were searched during August 2013. A track search was performed on February 27, 2014. Study was included in this review if it was: (1) a randomized controlled tri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
49
0
4

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(55 citation statements)
references
References 28 publications
2
49
0
4
Order By: Relevance
“…Within the meta-analysis of Wu et al the pooled VAS back and leg pain relief comparing interspinous spacers versus decompression alone did not find any significant differences [28]. In three of these investigations, however, the devices were inserted without decompression: X-Stop Ò (Medtronic Inc., Minneapolis, MN) [29], Aperius Ò (Medtronic, Switzerland) [30], and coflex Ò without decompression [25].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Within the meta-analysis of Wu et al the pooled VAS back and leg pain relief comparing interspinous spacers versus decompression alone did not find any significant differences [28]. In three of these investigations, however, the devices were inserted without decompression: X-Stop Ò (Medtronic Inc., Minneapolis, MN) [29], Aperius Ò (Medtronic, Switzerland) [30], and coflex Ò without decompression [25].…”
Section: Discussionmentioning
confidence: 99%
“…The investigations of Richter et al [22] and Kumar et al [24] did not find significantly different complication and revision rates of coflex Ò as adjunct to decompression compared to decompression alone. In the Moojen investigation, the complication and reoperation rate was reported to be higher for additional coflex Ò implantation compared to decompression alone and the possible reason was mentioned before [25,28]. The low complication rate might lead to the assumption of a general underreporting of complications and reoperations within the unmonitored registries.…”
Section: Sd Standard Deviationmentioning
confidence: 99%
“…The meta -analyses showed no significant difference on clinical outcomes in comparison with decompressive surgery. Additionally ISD has higher incidence of long -term reoperation and might lead to burden of cost [20,21]. Furthermore biomechanical changes such as decrease in ROM, and increase of interdiscal pressure and facet load at the adjacent segment following implantation of ISD are reported in both finite element and in vitro biomechanical studies [22,23].…”
Section: Discussionmentioning
confidence: 99%
“…Meta-analyses comparing standard decompression to IPDs have shown that IPDs are not as efficacious. Al-Min Wu et al conducted a retrospective study of IPD and laminectomy patients and found no significant difference between VAS and ODI improvements between the two groups but encountered a higher risk for reoperation in the IPD group during the 12-to 24-month follow-up period [28]. Patil et al compared IPD using X-STOP to laminectomy patients and found an increased risk of reoperation (12.6 vs. 5.8%, RR = 2.07) in the IPD cohort [29•].…”
Section: Literature Searchmentioning
confidence: 99%